The Miracle of Storry Telling - Yudi, Dede (Universitas Muhammadiyah Magelang, 2010)
There are three main approaches in early childhood, which is known by the acronym 3 B is playing, singing and storytelling. Telling stories or storytelling, an activity that anticipated and favored by younger children. Not only please the child, but also there are millions of miracles contained in them. Ironically, in some families, this activity is still less with the culture of watching television. Given the story or the storytelling is a miracle, then there is no other way, the family moved to Indonesia must get used to read a story and storytelling for her baby. Deep in their hearts, they whisper.